Analysis of the Community Diagnosis Program Conducted by Department of Community Medicine of Nobel Medical College Biratnagar - Bhandari, Buna; Bhattarai, Mahesh; Karna, Rajiv Ranjan; Jha, Nilambar (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 6-10 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8798